Analisis Dasar-Dasar Pendidikan Islam Berdasarkan Perspektif Filosofis, Akademis, Sosiologi, Politik, Dan Ekonomi - Azzahra, Radita; Handayani, Tutut; Zuhdiyah (CENDEKIA: Jurnal Studi Keislaman, 2024)
Islamic education is a system that makes learners able to exert their lives in accordance with what has become the goal and not out of Islamic law and then developed based on the basic abilities of learners towards the maximum point in growth and development. The method used in writing this article is using the Library Study Method (Library Reasearch). Library study is a method of collecting data by knowing and examining the theories created by scholars who have a connection with the research topic. The basics of Islamic education are things that include fundamental principles that become the basis for carrying out education. The aspects contained in Islamic Education are Philosophical aspects which are Academic aspects which are containers or institutions that practice learning activities critical thoughts that are needed in teaching and learning activities. Furthermore, the political aspect provides evidence of the government's seriousness in controlling the education system. There is also a sociological aspect as a mutual interaction between children, teachers, and the entire community in the school environment and finally the economic aspect which is often one of the factors inhibiting children's education in Indonesia